Evaluation of Fluoroquinolone Resistance in Clinical Avian Pathogenic Escherichia coli Isolates from Flanders (Belgium) - Robin Temmerman; An Garmyn; Gunther Antonissen; Gerty Vanantwerpen; Mia Vanrobaeys; Freddy Haesebrouck; Mathias Devreese (MDPI AG, 2020)
Fluoroquinolones are frequently used antimicrobials for the treatment of avian pathogenic Escherichia coli (APEC) infections. However, rapid development and selection of resistance to this class of antimicrobial drugs is a significant problem. The aim of this study was to investigate the occurrence and mechanisms of antimicrobial resistance against enrofloxacin (ENRO) in APEC strains in Flanders, Belgium. One hundred and twenty-five APEC strains from broilers with clinical colibacillosis were collected in Flanders from November 2017 to June 2018. The minimum inhibitory concentration (MIC) of all strains and the mutant prevention concentration (MPC) of a sample of sensitive isolates were determined using a commercial gradient strip test and via the agar dilution method, respectively. Non-wild type (NWT) isolates were further characterized using polymerase chain reaction (PCR), gel electrophoresis and gene sequencing. Forty percent of the APEC strains were NWT according to the epidemiological cut-off (ECOFF) measure (MIC > 0.125 μg/mL). With respect to clinical breakpoints, 21% were clinically intermediate (0.5 ≤ MIC ≤ 1 μg/mL) and 10% were clinically resistant (MIC ≥ 2). The MPC values of the tested strains ranged from 0.064 to 1 μg/mL, resulting in MPC/MIC ratios varying from 4 to 32. The majority (92%) of the NWT strains carried one or two mutations in gyrA. Less than a quarter (22%) manifested amino acid substitutions in the topoisomerase IV parC subunit. Only three of the NWT strains carried a mutation in parE. Plasmid mediated quinolone resistance (PMQR) associated genes were detected in 18% of the NWT strains. In contrast to the relatively large number of NWT strains, only a small percentage of APEC isolates was considered clinically resistant. The most common MPC value for sensitive strains was 0.125 μg/mL. Some isolates showed higher values, producing wide mutant selection windows (MSW). Chromosomal mutations in DNA gyrase and topoisomerase IV were confirmed as the main source of decreased antimicrobial fluoroquinolone susceptibility, de-emphasizing the role of PMQR mechanisms.